The Routledge Companion to Art in the Public Realm - Cartiere, Cameron; Tan, Leon (Routledge companions., 2020)
This multidisciplinary companion offers a comprehensive overview of the global arena of public art. It is organised around four distinct topics: activation, social justice, memory and identity, and ecology, with a final chapter mapping significant works of public and social practice art around the world between 2008 and 2018. The thematic approach brings into view similarities and differences in the recent globalisation of public art practices, while the multidisciplinary emphasis allows for a consideration of the complex outcomes and consequences of such practices, as they engage different disciplines and communities and affect a diversity of audiences beyond the existing 'art world'. The book will highlight an international selection of artist projects that illustrate the themes. This book will be of interest to scholars in contemporary art, art history, urban studies, and museum studies.